2022
DOI: 10.1111/mec.16642
|View full text |Cite
|
Sign up to set email alerts
|

Millennia‐old coral holobiont DNA provides insight into future adaptive trajectories

Abstract: Ancient DNA (aDNA) has been applied to evolutionary questions across a wide variety of taxa. Here, for the first time, we utilized aDNA from millennia‐old fossil coral fragments to gain new insights into a rapidly declining western Atlantic reef ecosystem. We sampled four Acropora palmata fragments (dated 4215 BCE to 1099 CE) obtained from two Florida Keys reef cores. From these samples, we established that it is possible both to sequence aDNA from reef cores and place the data in the context of modern‐day gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 96 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Siderastrea siderea reads were cleaned and demultiplexed following the de novo walkthrough (https://github.com/z0on/2bRAD_denovo/blob/master/2bRAD_README.sh). Because there is no genome for S. siderea , reads were first mapped to concatenated Symbiodiniaceae genomes (Dougan et al, 2022; Scott et al, 2022; Shoguchi et al, 2013, 2018) with bowtie2 version 2.4.5 (Langmead & Salzberg, 2012). Any mapped reads were discarded to remove symbiont contamination from coral host reads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siderastrea siderea reads were cleaned and demultiplexed following the de novo walkthrough (https://github.com/z0on/2bRAD_denovo/blob/master/2bRAD_README.sh). Because there is no genome for S. siderea , reads were first mapped to concatenated Symbiodiniaceae genomes (Dougan et al, 2022; Scott et al, 2022; Shoguchi et al, 2013, 2018) with bowtie2 version 2.4.5 (Langmead & Salzberg, 2012). Any mapped reads were discarded to remove symbiont contamination from coral host reads.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if the lineages previously described in Rippe et al (2021) were present at the second transect, 2bRAD raw sequences were processed following the same methods described in Rippe et al (2021) (Dougan et al, 2022;Scott et al, 2022;Shoguchi et al, 2013Shoguchi et al, , 2018 with bowtie2 version 2.4.5 (Langmead & Salzberg, 2012). Any mapped reads were discarded to remove symbiont contamination from coral host reads.…”
Section: Population Structure and Confirmation Of Lineagementioning
confidence: 99%
“…As in the case of dental calculus, mineralized structures are however more likely to preserve DNA for longer periods. Thus, Scott et al (2022) successfully extracted and sequenced DNA from millennia-old corals that revealed their original microbiomes which showed similarities to those from today. However, they identified very few sequences that could be affiliated to Symbiodiniaceae, which are essential eukaryotic phototrophic symbionts of corals.…”
Section: Zoological Collectionsmentioning
confidence: 99%
“…+ , 2017;Rogaev et al, 2006;Scott et al, 2022) and can lead to synthetic mtDNA plasmids that may be able to be injected for uptake by recipient mt populations (Gibson et al, 2010;Silva-Pinheiro & Minczuk, 2022). Native recipient mtDNAs could then be targeted for degradation (Jackson et al, 2020;Silva-Pinheiro & Minczuk, 2022; see Appendix S1).…”
Section: Appli C Ati On S Of Cmnrmentioning
confidence: 99%
“…Extinct haplotypes could replace extant ones with high mutational load, or simply provide more potentially‐adaptive variation on which selection can act. Recovery of ancient mtDNA sequences is possible from frozen remains, specimens, or continuous deposits (Anmarkrud & Lifjeld, 2017 ; Rogaev et al., 2006 ; Scott et al., 2022 ) and can lead to synthetic mtDNA plasmids that may be able to be injected for uptake by recipient mt populations (Gibson et al., 2010 ; Silva‐Pinheiro & Minczuk, 2022 ). Native recipient mtDNAs could then be targeted for degradation (Jackson et al., 2020 ; Silva‐Pinheiro & Minczuk, 2022 ; see Appendix S1 ).…”
Section: Applications Of Cmnrmentioning
confidence: 99%